PENERAPAN K-MEANS DALAM PENGELOMPOKAN DATA POLIS ASURANSI KENDARAAN BERMOTOR DI PT JASARAHARJA PUTERA - Utami, Winda Putri; Handoko, Koko (LPPM Universitas Putera Batam, 2020)
Motor Vehicle Insurance Policy is one of the insurance products at PT Jasaraharja Putera, being an insurance company certainly has a lot of data that causes that will only take place and make a large pile of records for that can be used to obtain information as product development and can be used as a target to get company income. The concept of the method used in this study is the K-Means Clustering method, this method is the most common and simple, which has the ability to group large enough data to be more efficient which aims to create information or add and find information from the data held. In this study the data is used to group Motor Vehicle Insurance Policy data from 2017 to 2019 apply the RapidMiner application. The test results obtained in the last iteration for the first cluster are 15 data, the second cluster is 6 data, the third cluster is 1 data, and the fourth cluster is 3 data. Based on the results of research on sample data, it can be seen that public interest in insurance is needed to develop insurance product marketing in order to increase the company's tagit and increase company revenue.